The Effect of Mordan Alum, Tunjung, and Betel Lime on the Ecoprint Outcomes of Star Fruit on Semi-Wool Materials - Sari, Diah Permata; Nelmira, Weni; Novrita, Sri Zulfia; Zamil, Ilham (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research is based on the use of star fruit leaves as an ecoprint motif using hammering techniques assisted by mordan and fixation. The purpose of this study is to describe the direction of the color name, determine the clarity of the shape of the motif, the color resistance to washing, and describe the influence of the use of alum, tunjung, and betel lime. The type of data is in the form of primary data with data collection techniques using research instruments in the form of questionnaires consisting of three teaching staff and 15 students. The data analysis technique with the Friedman K-Related Sample Test uses the SPSS program version 31.0. The direction of the color name is generated using the Colorblind Assistant application. The direction of the ecoprint color name uses star fruit leaves on semi-wool material. Mordan alum produces Golden Sundance color, Dark Brown tunjung mordan, and olive color betel lime mordan. The result of the clarity of the shape of the leaf motif on the alum and tunjung mordans produces a clear motif shape while the betel lime mordan produces a very clear motif shape on semi-wool materials. The color fade resistance to the washing of star fruit leaf ecoprint wuluh mordan alum at 1 wash 50% stated unchanged and 50% stated slightly changed, mordan tunjung 1 time wash 94.44% stated unchanged and betel lime mordan 1 wash 100% stated unchanged. The results of the best color fade resistance to washing are shown by betel lime mordan.